Effect of scientific learning approach on mathematical problem-solving ability of junior high school students - Saragi, Melyana; Ikashaum, Fertilia (LINEAR: Journal of Mathematics Education, 2024)
The scientific approach in learning at school aims to familiarize students with thinking, discussing and creating using scientific principles and steps. Therefore, the aim of this research is to increase student activity and find out how the scientific approach influences class students' problem solving abilities. VIII Kartikatama Metro Middle School. Through problem solving abilities students can develop students' thinking abilities to be able to connect the knowledge and skills that students already have to solve the problems given. This research is quantitative research. The research location is Kartikatama Metro Middle School. The subjects in this research were 25 experimental class students and 25 control class students. The data collection technique used was the Posttest test. Data analysis techniques are carried out by testing research instruments, analysis testing and hypothesis testing using the t test. Based on the research results, the Sig value was obtained. (2-tailed) is 0.11<0.05, which means that there is an influence of the scientific approach model through the problem solving abilities of class VIII students at SMP Kartikatama Metro or in other words the average problem solving ability of students in the experimental class is better than average - average problem solving ability of control class students.